2015
DOI: 10.1557/jmr.2015.70
|View full text |Cite
|
Sign up to set email alerts
|

Optical reflectance of alkali-textured silicon wafers with pyramidal facets: 2D analytical model

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…But for a while now, it has been a medium for study and research on solar energy courses taught at the department of Materials and Engineering. In addition, considering the fact that panel orientation is one of the fundamental factors that help determine the amount of light that can be harvested from the sun daily [46], [47], the orientations of the panels are set to the south at a tilt angle of 30° to enhance the panel's performance [46], [47]. The design of the entire system comprises of a rechargeable battery (for storage/backup) and light emitting diode (LED) lamp that is sufficient to operate for 10-11 hours daily [48], interconnecting cables (for battery and lamp), a solar photovoltaic module/panel, mounting structure, and charge controller.…”
Section: Description Of Site and Installationmentioning
confidence: 99%
See 1 more Smart Citation
“…But for a while now, it has been a medium for study and research on solar energy courses taught at the department of Materials and Engineering. In addition, considering the fact that panel orientation is one of the fundamental factors that help determine the amount of light that can be harvested from the sun daily [46], [47], the orientations of the panels are set to the south at a tilt angle of 30° to enhance the panel's performance [46], [47]. The design of the entire system comprises of a rechargeable battery (for storage/backup) and light emitting diode (LED) lamp that is sufficient to operate for 10-11 hours daily [48], interconnecting cables (for battery and lamp), a solar photovoltaic module/panel, mounting structure, and charge controller.…”
Section: Description Of Site and Installationmentioning
confidence: 99%
“…Conversely, the probability of survival ( ) can be determined from the following expression [46], [47]:…”
Section: Reliability Modelmentioning
confidence: 99%
“…In the case of monocrystalline silicon, a random upright pyramid texture, created by wet alkaline etching, is most commonly used. [15][16][17][18] This texture reduces reflectance and increases light trapping, and thus contributes to an increase in the current output of the solar cell 15,[19][20][21] and is also cheaper to realize than a perfectly planar substrate surface. In this paper, it is shown that such substrates coloured with single layer thin film coatings possess better angular colour stability than planar substrates coated with identical coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Texturing of the crystalline silicon wafer is usually one way to reduce reflection and enhance the absorbed light into the silicon substrate [9] and invariably, into the device [10], [11]. It is often achieved by using anisotropy etching to modify the surfaces of (100) silicon substrates into square-based pyramidal structures [12]. Potassium hydroxide (KOH) and isopropyl alcohol (IPA) are the most preferred alkaline solutions used for anisotropic etching of silicon substrates [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This allows researchers to effectively study the surface morphology of different surfaces such as in the case of textured silicon substrates that are used in solar cells applications [29][30][31][32][33][34][35]. In our previous studies [9], [12], scanning electron microscope (SEM) has been used to evaluate the morphology of textured sample after etching [9]. However, SEM does not readily yield quantitative information such as the height distributions, 3D profile images, etc.…”
Section: Introductionmentioning
confidence: 99%